2022
DOI: 10.1001/jamanetworkopen.2022.12246
|View full text |Cite|
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Rural-Urban Trends in 5-Year Survival of Patients With Lung, Prostate, Breast, and Colorectal Cancers: 1975-2011 Surveillance, Epidemiology, and End Results (SEER)

Abstract: IMPORTANCE Considering reported rural-urban cancer incidence and mortality trends, rural-urban cancer survival trends are important for providing a comprehensive description of cancer burden. Furthermore, little is known about rural-urban differences in survival trends by racial and ethnic groups.OBJECTIVE To examine national rural-urban trends in 5-year cancer-specific survival probabilities for lung, prostate, breast, and colorectal cancers in a diverse sample of racial and ethnic groups. DESIGN, SETTING, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Prior studies have observed associations between race/ethnicity or rural/urban status with both breast cancer outcomes and mortality [ 28 , 29 , 40 ]. Some studies have explored the rural–urban differences in breast cancer incidence [ 41 ], survival [ 42 ], mortality [ 28 , 29 , 43 ], and focused on specific regions, while the results of our current study aimed to illuminate a nationally representative relationship between race and rurality with several breast cancer outcomes. For instance, Moore et al (2018) observed that specifically for NH-black and Hispanic women, geographic areas of high breast cancer mortality or ‘hot spots’ were prevalent throughout the southeastern U.S. for NH-black women, and among Hispanic women within the southwest region of the U.S. [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have observed associations between race/ethnicity or rural/urban status with both breast cancer outcomes and mortality [ 28 , 29 , 40 ]. Some studies have explored the rural–urban differences in breast cancer incidence [ 41 ], survival [ 42 ], mortality [ 28 , 29 , 43 ], and focused on specific regions, while the results of our current study aimed to illuminate a nationally representative relationship between race and rurality with several breast cancer outcomes. For instance, Moore et al (2018) observed that specifically for NH-black and Hispanic women, geographic areas of high breast cancer mortality or ‘hot spots’ were prevalent throughout the southeastern U.S. for NH-black women, and among Hispanic women within the southwest region of the U.S. [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of colorectal cancer (CRC) is still the highest in the world, which seriously threatens people's health. 1 Cancer stem cells (CSCs) have directional differentiation and proliferation potential, and play an important role in tumor occurrence and development, tumor recurrence and clinical prognosis. 2 Through the sorting and identification of CRC cells in vitro, it can be found that CSC existence is an important factor to promote the malignant proliferation of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of colorectal cancer (CRC) is still the highest in the world, which seriously threatens people's health 1 . Cancer stem cells (CSCs) have directional differentiation and proliferation potential, and play an important role in tumor occurrence and development, tumor recurrence and clinical prognosis 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Original Investigation titled “Racial and Ethnic Differences in Rural-Urban Trends in 5-Year Survival of Patients With Lung, Prostate, Breast, and Colorectal Cancers: 1975-2011 Surveillance, Epidemiology, and End Results (SEER),” published May 19, 2022, there was an extra word in the Abstract and a misspelling in Dr Langston’s name in the Author Contribution section. This article has been corrected …”
mentioning
confidence: 99%